Practicalities of the use of fayalite slags for recovery of metals from urban wastes - J Chen; S Nicol; B Hogg; E Jak; S Nikolic (The Australasian Institute of Mining and Metallurgy, 2024)
The quantity of post-consumer ‘waste’ materials generated each year is rapidly increasing. These materials can contain significant quantities of critical metals and present an environmental challenge if landfilled. The ISACYCLE™ technology is a proven solution for the processing of these materials. In the ISACYCLE™ furnace, the post-consumer materials are processed to recover energy along with any contained critical metals, in the form of a base metal alloy or matte. In addition, a clean aggregate (slag) is generated, which has the potential to be used for a range of applications in the construction industry. This slag is commonly based on a fayalite slag but is modified to manage the complex feed. This paper will review the fayalite slag system and the theoretical modifications required for treating urban wastes. Slags from an ISACYCLE™ furnace processing urban wastes have been sampled and characterised. The chemistry of these samples will be reviewed and compared to the expected theoretical modifications required.